2015
DOI: 10.3109/0886022x.2015.1052945
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hypervolemia, left ventricular hypertrophy and fibroblast growth factor 23 in hemodialysis patients

Abstract: Our study showed that interdialytic volume overload increased both LVMI and FGF-23 values. We can consider that interdialytic volume control exerts positive effects on increased FGF-23 levels which predict the negative cardiovascular outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
3
18
1
Order By: Relevance
“…The immediate effect of FGF23 is lowering of serum phosphate which in our study was only modest, but has been demonstrated in other studies (Table 4). A potential longer term effect of concern is that higher levels of FGF23 are associated with both cardiovascular events and death in advanced CKD [23] and that FGF23 is associated with left ventricular hypertrophy (LVH) in human studies [24]. Experimental studies have identified that the LVH associated with elevated FGF23 serum levels and mediated by its specific cardiac receptor (Type 4) can be mitigated by blocking the receptor [25].…”
Section: Discussionmentioning
confidence: 99%
“…The immediate effect of FGF23 is lowering of serum phosphate which in our study was only modest, but has been demonstrated in other studies (Table 4). A potential longer term effect of concern is that higher levels of FGF23 are associated with both cardiovascular events and death in advanced CKD [23] and that FGF23 is associated with left ventricular hypertrophy (LVH) in human studies [24]. Experimental studies have identified that the LVH associated with elevated FGF23 serum levels and mediated by its specific cardiac receptor (Type 4) can be mitigated by blocking the receptor [25].…”
Section: Discussionmentioning
confidence: 99%
“…59 In the case of FGF23, we have only indirect evidence in the form of increased cardiovascular mortality in CKD patients, including those on dialysis, with higher concentrations of FGF23 in the circulation. 60 It would, therefore, be expected that higher concentrations of sclerostin, like those of FGF-23, should increase cardiovascular risk, but there is conflicting evidence. 61 Some studies show no association between sclerostin and mortality.…”
Section: Sclerostin In Chronic Kidney Diseasementioning
confidence: 99%
“…In addition to the traditional risk factors for heart disease such as diabetes and hypertension, patients with ESRD have risk factors that make them at greater risk for SCD, including a higher prevalence of left ventricular hypertrophy and vascular calcification [3]. Bleyer et al [4] examined the timing of SCD in a cohort of patients from five hemodialysis units in the southeastern United States and reported a 1.71 ratio of observed to expected sudden deaths in the 12 h following the onset of a hemodialysis session.…”
Section: Introductionmentioning
confidence: 99%